2001
DOI: 10.1074/jbc.m102865200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Linear Amphipathic β-Sheet Cationic Antimicrobial Peptide with Enhanced Selectivity for Bacterial Lipids

Abstract: All known naturally occurring linear cationic peptides adopt an amphipathic ␣-helical conformation upon binding to lipids as an initial step in the induction of cell leakage. We designed an 18-residue peptide, (KIGAKI) 3 -NH 2 , that has no amphipathic character as an ␣-helix but can form a highly amphipathic ␤-sheet. When bound to lipids, (KIGAKI) 3 -NH 2 did indeed form a ␤-sheet structure as evidenced by Fourier transform infrared and circular dichroism spectroscopy. The antimicrobial activity of this pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
149
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(162 citation statements)
references
References 38 publications
13
149
0
Order By: Relevance
“…This idea is supported by our observation that all peptides tested that conform to the active motif have comparable poreforming activity. Similarly, other authors have shown that antimicrobial activity of pore-forming peptides can be surprisingly insensitive to alterations in sequence, length, or even secondary structure (21,22). New libraries need to be screened with framework sequences based on the pore-forming motif identified in this work.…”
Section: Resultsmentioning
confidence: 99%
“…This idea is supported by our observation that all peptides tested that conform to the active motif have comparable poreforming activity. Similarly, other authors have shown that antimicrobial activity of pore-forming peptides can be surprisingly insensitive to alterations in sequence, length, or even secondary structure (21,22). New libraries need to be screened with framework sequences based on the pore-forming motif identified in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Although CD spectra recorded in the presence of lipid systems only provide a weighed average of the membrane-bound and free peptide conformations, both conventional CD and oriented circular dichroism (OCD) have been proven useful for the analysis of peptide conformational changes upon interaction with model membranes. 27,31,32,41,42 We herein report the study of the interactions between the antimicrobial peptides CA(1-8)M(1-18) and CA(1-7)M(2-9) and large unilamellar vesicles (LUVs) of three different lipid bilayer systems: zwitterionic DMPC, anionic DMPG, and a DMPC/DMPG 3:1 mixture. The study was carried out by DSC, QELS, and CD, so that the effect of the peptides on vesicle thermotropic phase behavior (DSC), charge, and size (QELS) could be related to membrane-induced changes in peptide structure (CD).…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, it is known that a low concentration of peptides does not exert any antimicrobial effect, below a threshold concentration. For PGLa and similar model peptides, about 1 peptide per 30 lipids was needed to get an atnimicrobial effect (32). It would, thus, be interesting to vary the peptide/lipid molar ratio (P/L) and study the peptide-peptide interactions emerging at higher peptide concentrations, but this is not easily done in micelles.…”
Section: Structures In Micellesmentioning
confidence: 99%